Feasibility and challenges of inpatient psychotherapy for psychosis: lessons learned from a veterans health administration pilot randomized controlled trial. (December 2016) - Boden, Matthew; Gaudiano, Brandon; Walser, Robyn; Timko, Christine; Faustman, William; Yasmin, Sarah; Cronkite, Ruth; Bonn-Miller, Marcel; McCarthy, John
Abstract Background In large health care systems, decision regarding broad implementation of psychotherapies for inpatients with psychosis require substantial evidence regarding effectiveness and feasibility for implementation. It is important to recognize challenges in conducting research to inform such decisions, including difficulties in obtaining consent from and engaging inpatients with psychosis in research. We set out to conduct a feasibility and effectiveness Hybrid Type I pilot randomized controlled trial of acceptance and commitment therapy (ACT) and a semi-formative evaluation of barriers and facilitators to implementation. Findings We developed a training protocol and refined an ACT treatment manual for inpatient treatment of psychosis for use at the Veterans Health Administration. While our findings on feasibility were mixed, we obtained supportive evidence of the acceptability and safety of ACT. Identified strengths of ACT included a focus on achievement of valued goals rather than symptoms. Weaknesses included that symptoms may limit patient's understanding of ACT. Facilitators included building trust and multi-stage informed consent processes. Barriers included restrictive eligibility criteria, rigid use of a manualized protocol, and individual therapy format. Conclusions are limited by our randomization of only 18 patient participants (with nine completing all aspects of the study) out of 80 planned. Conclusions Future studies should include (1) multi-stage informed consent processes to build trust and alleviate patient fears, (2) relaxation of restrictions associated with obtaining efficacy/effectiveness data, and (3) use of Hybrid Type II and III designs.